Strategic continuous process improvement which quality tools to use, and when to use them - Plenert,Gerhard (McGraw Hill, 2012)
Resolve "quality chaos" by creating a link between quality problems and their optimal solutions. With a focus on building an integrated quality environment, Strategic Continuous Process Improvement: Which Quality Tools to Use and When to Use Them begins by discussing the different types of continuous process improvement (CPI) systems available. This practical guide explains how to implement a strategic performance model and select and integrate appropriate metrics to achieve desired results. Tested techniques for executing an improvement process are included along with real-world examples. The book concludes with a plan to help you sustain an ongoing culture of continuous quality improvement in your organization. Find out how to: -Identify CPI opportunities -Evaluate various CPI options using comparative benchmarks -Understand the characteristics of each quality option -Map CPI characteristics against quality problems -Select the appropriate tool to fit a specific quality problem -Recognize the role of governance and performance reviews -Cascade and communicate CPI throughout your organization -Move the needle toward successful process optimization